Histone Deacetylase Inhibitors as Cancer Therapeutics - Grant, Steven; ScienceDirect eBooks (Amsterdam : Elsevier, 2012)
Advances in Cancer Research provides invaluable information on the exciting and fast-moving field of cancer research. This thematic volume looks at "Histone Deacetylase Inhibitors as Cancer Therapeutics." Provides invaluable information on the exciting and fast-moving field of cancer researchThis thematic volume looks at "Histone Deacetylase Inhibitors as Cancer Therapeutics"Outstanding and original reviews.
Text in English.
Includes bibliographical references and index.
Elsevier
Keywords: Histone deacetylase; Cancer -- Research; Cancer -- Treatment; Histone deacetylase; Cancer -- Research; Cancer -- Treatment; Histone Deacetylase Inhibitors -- therapeutic use; Biomedical Research; Electronic books